Beyond words: analyzing non-verbal communication techniques in a medical communication skills course via synchronous online platform - Ismail, Noor Akmal Shareela; Mageswaran, Nanthini; Bujang, Siti Mariam; Awang Besar, Mohd Nasri (Frontiers in Medicine, 2024)
Background: Effective doctor-patient relationships rely on robust communication skills, yet nonverbal communication techniques (NVC) are often overlooked, especially in online synchronous interactions. This study examines NVC types during online feedback sessions in a medical education module. Methodology: A group of 100 first-year medical students and ten lecturers at Universiti Kebangsaan Malaysia engaged in communication skills activities via Microsoft Teams. Sessions were recorded, and lecturer NVC, including body position, facial expressions, voice intonation, movements, eye contact, and paralinguistics, were observed. Students provided reflective writings focusing on observed NVC. Results: Consistent NVC patterns were identified during feedback sessions, with lecturers predominantly leaning forward, maintaining eye contact, and exhibiting dynamic voice intonation. They frequently used tactile gestures and filler sounds like "um" and "okay." Less observed NVC included body touching and certain paralinguistic cues. Initial student apprehension transformed positively upon observing the lecturer's expressions, fostering an open reception of feedback. Students also preferred comfortable learning environments for feedback reception. Despite limitations such as potential contrivances due to lecturer awareness of being recorded and the small sample size, the study emphasizes the need for integrating NVC training into medical school curricula. The findings highlight the importance of effective NVC during online feedback sessions, crucial for conveying nuanced information. Ongoing professional development is essential for educators to enhance proficiency in utilizing NVC techniques in virtual learning environments. Conclusion: Future research directions include longitudinal investigations into NVC patterns, comparative analyses across disciplines, cross-cultural examinations, interventions to improve NVC skills, exploration of technology's role in NVC enhancement, qualitative studies on student perceptions, and interdisciplinary collaborations to deepen understanding of NVC in virtual learning environments.